Differences, relationships, and risks of using digital technology with depression, anxiety, and stress during the COVID-19 pandemic - Hasanatuludhhiyah, Nurina; Sawitri, Brihastami; Rahman, Beny Aji Ifaudi; Atika, Atika; Yulianti, Erikavitri; Marchianti, Ancah Caesarina Novi; Visuddho, Visuddho (Journal of Ideas in Health, 2025)
Background: The COVID-19 pandemic highlighted the critical need for mental health resilience and digital inclusion, particularly among vulnerable populations. To draw lessons from the pandemic for future public health initiatives, this study examined the mental health status of middle-aged and older Indonesians and its associations with sociodemographic factors, comorbidities, grief experiences, and digital technology use. Methods: This cross-sectional study was conducted during the second wave of the COVID-19 pandemic (September–October 2021). An online questionnaire collected data on sociodemographic variables, comorbidities, grief experiences, and digital technology usage. Mental health was assessed using the Depression, Anxiety, and Stress Scale-21 (DASS-21). Results: From total 199 enrolled in this study, prevalence rates for depression, anxiety, and stress were 11.1%, 33.7%, and 19.5%, respectively. Depression was associated solely with marital status, while anxiety was influenced by marital status, comorbidities, and the use of digital technology for health information access (p<0.05). Stress was impacted by gender, marital status, comorbidities, and digital technology usage (p<0.05). Multivariate analysis confirmed that infrequent digital technology use predicted higher levels of depression and anxiety (aOR, 2.82, CI 1.14-6.96; 2.36, CI 1.26-4.43; p<0.05). Females, unmarried individuals (aOR, 2.38, CI 1.08-5.25; 2.37, CI 1.11-5.09; p<0.05), and those with comorbidities were at greater risk for mental health challenges (aOR, 3.92, CI 1.43-10.75; p<0.05). However, inadequate digital technology skills were linked to lower stress likelihood (aOR, 0.37, CI 0.144-0.95; p<0.05). Conclusion: This study underscores the importance of bridging the digital gap and addressing social determinants to strengthen mental health resilience among middle-aged and older adults in Indonesia. Post-pandemic, integrating digital inclusion strategies into public health initiatives is vital for fostering equitable mental health outcomes.